Dampak Penerapan Sport Education Model terhadap Hasil Belajar PJOK - Herdis Targiansah; Cucu Hidayat; Dicky Tri Juniar (Jurnal MensSana, 2025)
This study aims to analyze the impact of implementing the Sport Education Model (SEM) on students’ learning outcomes in Physical Education at SMA Negeri 1 Kota Tasikmalaya. The research was conducted in response to the need for more authentic, student-centered, and engaging instructional models that enhance the quality of Physical Education learning. Using an ex post facto design, the study employed a random class sampling technique to select participants, consisting of two groups: students taught using SEM and those taught through conventional methods. Learning outcomes were obtained from teachers’ assessment records, covering cognitive, affective, and psychomotor domains. Data analysis included normality and homogeneity tests followed by an independent samples t-test. The findings revealed a significant difference between the two groups, with the SEM group achieving higher mean learning outcomes than the non-SEM group. These results indicate that SEM is effective in improving student learning outcomes by fostering motivation, engagement, and meaningful learning experiences. The study recommends broader and more systematic implementation of SEM in Physical Education to further enhance student achievement